2017
DOI: 10.1016/j.amjsurg.2017.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for conversion of laparoscopic cholecystectomy to open surgery – A systematic literature review of 30 studies

Abstract: A detailed critical review of studies of prediction models and risk stratification for conversion from laparoscopic to open cholecystectomy is presented. One study is identified of high quality with a potential to be used in clinical practice, and external validation of this model is recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
110
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 53 publications
(130 reference statements)
6
110
3
5
Order By: Relevance
“…Stanisic et al reported significantly higher difficulty during LC in diabetics while Raman et al and Ibrahim et al too found diabetes mellitus to be an important risk factor. 12,7 Author found significant correlation of rising BMI with increasing duration of surgery with the highest mean of 64.38 min in those with BMI >30kg/m 2 and lowest mean of 52.50 min in those with BMI <20kg/m conversion of 7.69% in their patients having BMI >30kg/m 2 was also significantly higher than in the remaining patients. 8 out of 19 studies reviewed by Hu et al concluded that high BMI is an important risk factor for conversion.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Stanisic et al reported significantly higher difficulty during LC in diabetics while Raman et al and Ibrahim et al too found diabetes mellitus to be an important risk factor. 12,7 Author found significant correlation of rising BMI with increasing duration of surgery with the highest mean of 64.38 min in those with BMI >30kg/m 2 and lowest mean of 52.50 min in those with BMI <20kg/m conversion of 7.69% in their patients having BMI >30kg/m 2 was also significantly higher than in the remaining patients. 8 out of 19 studies reviewed by Hu et al concluded that high BMI is an important risk factor for conversion.…”
Section: Discussionmentioning
confidence: 93%
“…8 16 out of 30 studies reviewed by Hu et al found that older age, more than 60 years or 65 years, was an important risk factor and patients >65 years had three to five-fold chance of conversion to OC. 7 Philip Rothman et al in their meta-analysis concluded that quality of evidence for age as a risk factor for conversion was low. 9 Kanakala et al found significantly higher cardiorespiratory complications and conversion to OC amongst older patients in univariate analysis, but age became nonsignificant when other factors were adjusted for in multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations